Novel multi-stage aluminium production: part 1 – thermodynamic assessment of carbosulphidation of Al2O3/bauxite using H2S and sodiothermic reduction of Al2S3. Issue 2 (3rd April 2018) - Rhamdhani, M. A.; Huda, N.; Khaliq, A.; Brooks, G. A.; Monaghan, B. J.; Sheppard, D. A.; Prentice, L.
ABSTRACT: A novel multi-stage Al production through a carbosulphidation of Al2 O3, followed by a sodiothermic reduction of Al2 S3, was proposed. In Stage-1, alumina (or bauxite) is reduced to Al2 S3 in the presence of carbon and H2 S. In Stage-2, Al2 S3 is reduced to Al through reactions with Na or NaH. The thermodynamic analysis predicted Al2 S3 to be the main intermediate Al-compound when H2 S is reacted with Al2 S3 and C at 1000-2000°C at 1 atm. Al2 S3 formation was predicted to be low at 1100-1300°C at 1 atm (0.1 moles/mole Al2 O3 ) but increased with increasing temperature (0.96 moles/mole Al2 O3 at 1800°C). The thermodynamic analysis of sodiothermic reduction predicted that Al metal can be extracted from Al2 S3 below 800°C at 1 atm. The Na2 S produced can be hydrolysed to form H2 S and NaOH. H2 S can be re-used and the Na can be reproduced from NaOH and put back into the process.